Funding patterns for biomedical research and infectious diseases burden in Gabon - Olouyomi Scherif Adegnika; Yabo Josiane Honkpehedji; Fabrice Mougeni Lotola; Selidji Todagbe Agnandji; Ayola Akim Adegnika; Bertrand Lell; Elisa Sicuri (BMC, 2021)
Abstract Background Biomedical research plays an important role in improving health. There seems to exist a negative correlation between the amount of biomedical research funding and disease burden from all Sub-Saharan African countries. In this study, we describe funding patterns for biomedical research, explore the correlation between funding and burden of diseases, and quantify inequalities in funds distribution across diseases in Gabon over the period 2005-2015. Methods Data on medical research funds from 2005 to 2015 were retrieved through a structured questionnaire distributed to Gabonese biomedical research institutions and by consulting online databases. Data on the burden of diseases were gathered from the World Health Organization and the Institute for Health Metrics and Evaluation. We used Kendall rank correlation coefficient to explore the correlation between cumulative funds over time and the burden of disease. The inequality distribution of funding across diseases was assessed through Gini coefficient and Lorenz curve. Results Biomedical research funding was characterized by a remarkable growth from 2005 to 2010 and a decline from 2010 to 2014. Funds were mostly from external sources and from partnerships. There was inequality in research funds allocation across diseases and malaria was far the most funded disease. There was a significant negative correlation between cumulative funding and the burden of HIV, tuberculosis, and of Helminthiasis (from 2006 to 2010) suggesting that research may be contributing to the management of such diseases. A positive, although not significant, correlation was found between cumulative funds and malaria burden. Conclusions The negative correlation between HIV and tuberculosis cumulative funding and burden suggests that research may be contributing to the management of such diseases but further research is needed to assess the causal direction of such as relationship. As the burden of non-communicable diseases is increasing, more research funds should be focused on those. While research partnerships have been and will remain fundamental, Gabon should increase the amount of national funds to overcome periods of reduced research funding flows from abroad.